Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1029/92gl00022
|View full text |Cite
|
Sign up to set email alerts
|

A new Mesozoic isochron chart of the northwestern Pacific Ocean: Paleomagnetic and tectonic implications

Abstract: A new Mesozoic isochron chart of the northwestern Pacific Ocean has been completed by utilizing all the currently available data from 357 cruises. Our chart provides the first whole view of the Mesozoic magnetic anomaly lineations in the northwestern Pacific Ocean and yields essential information for understanding the problems of the Mesozoic magnetostratigraphic time scale and the evolutional history of the Pacific plate. The Mesozoic magnetostratigraphic time scale must be recalibrated using not only the Haw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 21 publications
2
72
0
Order By: Relevance
“…1) on the surrounding oceanfloor (NAKANISHI et al, 1989(NAKANISHI et al, , 1992. The ocean-floor on which this seamount chain is situated was formed between M14 and M11 (about 138 and 133 Ma) period according to KENT and GRAD-STEIN'S (1985) time scale.…”
Section: Geologic Settingmentioning
confidence: 99%
“…1) on the surrounding oceanfloor (NAKANISHI et al, 1989(NAKANISHI et al, , 1992. The ocean-floor on which this seamount chain is situated was formed between M14 and M11 (about 138 and 133 Ma) period according to KENT and GRAD-STEIN'S (1985) time scale.…”
Section: Geologic Settingmentioning
confidence: 99%
“…1). Nakanishi et al (1992b) identified Anomaly M22 near this portion of the Marshalls. Using the time scale of Harland et al (1990), the crust beneath Limalok is -155 m.y.…”
Section: Guyot Descriptions and Comparisons To Modern Analogsmentioning
confidence: 99%
“…1). Extrapolation of magnetic lineations identified to the south of these two edifices (Nakanishi et al, 1992b) produces an estimated plate age of >160 m.y. using the time scale of Harland et al (1990).…”
Section: Guyot Descriptions and Comparisons To Modern Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Japanese Lineation set, which is a Mesozoic magnetic anomaly lineation, exists in the East Mariana Basin, east of the Mariana Trench (Nakanishi et al 1992a), leading Nakanishi et al (1992b) to propose that the subducting plate along the southern part of the Mariana Trench is a part of the Pacific plate formed in the Mesozoic. The Japanese Lineation set has two strikes.…”
Section: Topographic Features Around the Challenger Deepmentioning
confidence: 99%